Treatment of postdural puncture headache - Fesenko, V. S.; Fesenko, U. A. (Pain medicine, 2017)
Postdural puncture headache may be complicated with hearing or visual disturbancies, intracranial subdural or intracerebral hematoma, cerebral herniation, and death. Thus, any case of postdural puncture headache should be taken into account seriously. Current noninvasive treatment of postdural puncture headache, including bed rest, fluids, analgesics, caffeine, and sumatriptan, is scarcely effective. Surgical closure of the dural tear remains an option of last resort. Epidural blood patch remains the invasive treatment of choice, with approximately 70 % prolonged success after initial injection. Old-fashioned intravenous aquatherapy is less invasive and rather popular among Ukrainian obstetric anesthesiologists. The pterygopalatine ganglion blockade is the least invasive treatment deserving further investigation.